USP7 Attenuates Endoplasmic Reticulum Stress and NF-κB Signaling to Modulate Chondrocyte Proliferation, Apoptosis, and Inflammatory Response under Inflammation. (6th April 2022) - Dong, Xiaofei; Yang, Chang; Luo, Yao; Dong, Wei; Xu, Xiaoxiao; Wu, Yanru; Wang, Jiawei
Abstract : The purpose of this research was to observe the functions and mechanisms of ubiquitin-specific peptidase 7 (USP7) on chondrocytes under tumor necrosis factor alpha- (TNF- α -) induced inflammation. Knee osteoarthritis (OA) models of mice were constructed by anterior cruciate ligament transection. The knee joint of mice was observed by histological staining, and the expression of USP7 was measured by immunohistochemistry staining. After knocking down or inhibiting USP7, chondrocyte proliferation was measured by histological staining and the CCK-8 assay; apoptosis was measured by western blot, flow cytometry, Caspase-3 activity, and TUNEL staining; and inflammatory response was measured by qRT-PCR and ELISA. The 4-phenylbutyric acid (4-PBA), siRNA of CHOP (si-CHOP), and QNZ were used to verify the signaling pathways. It was found that USP7 was reduced in the knee joint cartilage of OA mice. The knockdown of USP7 or its inhibitor decreased chondrocyte proliferation and accelerated apoptosis and inflammatory response under inflammation. The USP7 inhibitor exacerbated cartilage destruction in mice with OA. The knockdown of USP7 or its inhibitor activated the BiP-eIF2 α -ATF4-CHOP signaling of endoplasmic reticulum stress (ERS) and NF- κ B/p65 signaling. 4-PBA, si-CHOP, and QNZ partly reversed chondrocyte proliferation, apoptosis, and inflammatory response caused by USP7 knockdown. In conclusion, through inhibiting the BiP-eIF2 α -ATF4-CHOP signaling of ERS and NF- κ B/p65 signaling, USP7 promotes chondrocyte proliferation and suppresses the apoptosis and inflammatory response under TNF- α -induced inflammation.